Islamophobia in the USA, a case study of Pamela Gellar - Dr. Saeed ur Rahman,; Dr. Kalsoom Pracha,; Nazish Umer,; Sumera Safdar,; Maria Abbas,; Tahira Naz, (Al-Qanṭara, 2023)
The word Islamophobia is a modern term that refers to Islam as a bigoted religion, but the word was commonly used after 9/11 in 2001. In this way, the fear of Islam is instilled in the hearts of new generations and it is Psychological fear has become a disease, so this psychological disease is called Islamophobia. After the terrible tragedy of 9/11 in 2001, the already established welfare institutions in the United States turned towards Islam, and people like Pamela Geller, a Jewish woman who was afraid of Islam, read the holy book with the intention of criticizing the teachings of the Holy Quran, the main source of Islam. Pamela Geller wants to save America from Islam. To achieve this goal, Pamela took practical steps to explain the wrong meaning of the teachings of Islam in America. Pamela Geller came to the world by opening up in the field of Islamophobia. She founded the fear and hateful organization (SIOA) stop Islamization of America under the formal anti-Islam cause. The purpose of SIOA is to link terrorism to Islam, close Islamic schools, to support the protection of the life of the apostates, and presenting the teachings of the Quran as a justification for terrorism and especially supporting Israel. Pamela held a Muhammad cartoon contest and raised objections by explaining the wrong meaning of a verse of the Holy Quran. In this paper, the performance of Pamela's organization is described and Pamela's objections to the Qur'an are refuted by the teachings of the Qur'an.